A Gamified Wordwall Approach to Arabic Language Learning Evaluation: Integrating the MDA and PBL Frameworks - Achmad Farouq Abdullah; Sofwan Manaf; Tutik Lestari; Nesa Novrizal; Ulfatun Wahidatun Nisa (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2026)
Conventional Arabic assessment in pesantren remains dominated by memorisation-based, manually scored tests that limit student engagement and delay feedback. This study examines how a gamified Wordwall evaluation model, designed through the Mechanics–Dynamics–Aesthetics (MDA) framework and combined with Problem-Based Learning (PBL, can improve both the practice and the management of Arabic language learning evaluation. Using a two-cycle Classroom Action Research (CAR) design, the study involved 30 first-year santri of the TMI program at Pesantren Darunnajah. Data were collected through validated observation sheets, Wordwall-based achievement tests, and a perception questionnaire, and analysed using descriptive statistics, normalised gain (N-gain), and a paired-sample t-test. Learning activity rose from a pre-cycle baseline to 58.4% (Cycle I) and 82.2% (Cycle II); the mean achievement score increased from 72 to 86 and mastery from 63% to 90%, a statistically significant improvement (N-gain = 0.50, moderate). From a managerial perspective, automated scoring and real-time analytics reduced grading time and feedback latency and improved record accuracy. The novelty of the study lies in integrating Wordwall, MDA, and PBL into a single, data-driven evaluation model rather than treating gamification as a motivational add-on. The study concludes that the model offers a replicable, evidence-informed approach to modernising Arabic evaluation governance in Islamic boarding schools, within the limits of its single-site, small-sample design.